Do multiple physiological OCT biomarkers indicate age-related decline in rod mitochondrial function in C57BL/6J mice? - Goodman, Cole; Podolsky, Robert H.; Childers, Karen Lins; Roberts, Robin; Katz, Ryan; Waseem, Rida; Paruchuri, Anuhya; Stanek, Josh; Berkowitz, Bruce A. (Frontiers in Neuroscience, 2023)
Purpose To test the hypothesis that rod photoreceptor mitochondria function in vivo progressively declines over time. Methods 2, 12, and 24 month-old dark- and light-adapted C57BL/6J (B6J) mice were examined by OCT. We measured (i) an index of mitochondrial configuration within photoreceptors measured from the profile shape aspect ratio (MCP/AR) of the hyperreflective band posterior to the external limiting membrane (ELM), (ii) a proxy for energy-dependent pH-triggered water removal, the thickness of the ELM-retinal pigment epithelium (ELM-RPE), and its correlate (iii) the hyporeflective band (HB) signal intensity at the photoreceptor tips. Visual performance was assessed by optokinetic tracking. Results In 2 and 24 month-old mice, MCP/AR in both inferior and superior retina was smaller in light than in dark; no dark–light differences were noted in 12 month-old mice. Dark-adapted inferior and superior, and light-adapted superior, ELM-RPE thickness increased with age. The dark–light difference in ELM-RPE thickness remained constant across all ages. All ages showed a decreased HB signal intensity magnitude in dark relative to light. In 12 month-old mice, the dark–light difference in HB magnitude was greater than in younger and older mice. Anatomically, outer nuclear layer thickness decreased with age. Visual performance indices were reduced at 24 month-old compared to 2 month-old mice. Conclusion While the working hypothesis was not supported herein, the results raise the possibility of a mid-life adaptation in rod mitochondrial function during healthy aging in B6J mice based on OCT biomarkers, a plasticity that occurred prior to declines in visual performance.